Prevention of fall-related injuries in the elderly: An Eastern Association for the Surgery of Trauma practice management guideline. Issue 1 (July 2016) - Crandall, Marie; Duncan, Thomas; Mallat, Ali; Greene, Wendy; Violano, Pina; Christmas, A. Britton; Barraco, Robert
Abstract : BACKGROUND: Fall-related injuries among the elderly (age 65 and older) are the cause of nearly 750, 000 hospitalizations and 25, 000 deaths per year in the United States, yet prevention research is lagging. Using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology, the Eastern Association for the Surgery of Trauma produced this practice management guideline to answer the following injury prevention–related population, intervention, comparator, outcomes (PICO) questions: PICO 1: Should bone mineral–enhancing agents be used to prevent fall-related injuries in the elderly? PICO 2: Should hip protectors be used to prevent fall-related injuries in the elderly? PICO 3: Should exercise programs be used to prevent fall-related injuries in the elderly? PICO 4: Should physical environment modifications be used to prevent fall-related injuries in the elderly? PICO 5: Should risk factor screening be used to prevent fall-related injuries in the elderly? PICO 6: Should multiple interventions tailored to the population or individual be used to prevent fall-related injuries in the elderly? METHODS: A comprehensive search and review of all the available literature was performed. We used the GRADE methodology to assess the breadth and quality of the data specific to our PICO questions. RESULTS: We reviewed 50 articles that met our inclusion and exclusion criteria as they applied to our PICO questions. CONCLUSION: Given the data constraints, we offer the following suggestions and recommendations: PICO 1: We conditionally recommend vitamin D and calcium supplementation for frail elderly individuals. PICO 2: We conditionally recommend hip protectors for frail elderly individuals, in the appropriate environment. PICO 3: We conditionally recommend evidence-based exercise programs for frail elderly individuals. PICO 4: We conditionally recommend physical environment modification for frail elderly people. PICO 5: We conditionally recommend frailty screening for the elderly. PICO 6: We strongly recommend risk stratification with targeted comprehensive risk-reduction strategies tailored to particular high-risk groups. LEVEL OF EVIDENCE: Systematic review, level III.